A, The outcome of steriod resistant nephrotic syndrome of children in central teaching hospital of pediatrics: article - Hasan, Faleeha Obaid; Al Ubaidy, Mohamed Saad Fadhil; Murad, Haider Sabri (Karbala Journal of Medicine, 2022)
OUTCOME OF IDIOPATHIC STEROID RESISTANT NEPHROTIC SYNDROME OF CHILDREN IN CENTRAL TEACHING HOSPITAL OF PEDIATRICS Abstract Background: Steroid resistant nephrotic syndrome accounts for 10%-20% of all cases of idiopathic nephrotic syndrome. These patients are at risk of developing end stage renal disease. Aim of the study: to determine the demographic characteristics, renal biopsy findings, response to immunosuppressive treatment, and outcome in pediatric patients with steroid resistant nephrotic syndrome. Materials and Methods: This retrospective study included 136 children patients diagnosed as primary steroid resistant nephrotic syndrome followed by pediatric nephrology department in central teaching hospital of pediatric during the period from 2000 to December 2015.the study done from June 2016 to December 2016.Age at first episode, gender and familial history of nephrotic syndrome were recorded. Demographic characteristics, clinical features at presentation, renal biopsy findings, response to immunosuppressive treatment and outcome were analyzed. Results: one hundred thirty six patients involved in the study, Mean age at first episode of nephrotic syndrome was 7.18+_ 3.9 years (range: 1 - 16 years). renal biopsy was done for 83 patients and main histopathology was focal segmental glomerulosclerosis found in 54 patients represent (65.1%).Many items of drugs given to the patients and most common used and most effective drug is Cyclosporine A in which 34(34%) from patients achieved complete remission. There were 21 patients (15.4%) get complete remission, 38 patients (27.9%) lost follow up, 6 patients (4.4%) died, 13 patients (9.6%) developed stage 3 chronic kidney disease 24 patients (17.6%) developed stage 4 Chronic kidney disease and 34(25%) patients developed End stage renal disease. There is significant relationship between hypertension, hematuria, and impaired renal functions at presentation and response to immunotherapy and development of end stage renal disease ,while there is no significant relationship between age of patient at presentation, gender and histopathology with development of end stage renal disease. Conclusion: we found near half of the patients developed chronic renal failure and 25% developed end stage renal disease. Patients with atypical presentation, resistance to immunosuppressive are liable to develop End stage renal disease significantly .In addition, we found Cyclosporine A is more effective than other immunotherapy as the initial therapy for many patients. However, did not find relation between histopathology and progression to End stage renal disease. Key wards: steroid resistant nephrotc syndrome, cyclosporine A, chronic kidney disease, end stage kidney disease.